Solomon Schechter's Art of Hasidism: Tradition, Parody, and Transmission - Starr, David B. (The Jewish quarterly review, 2018)
This paper introduces and explores the earliest extant work by Solomon Schechter (1847-1915). The conventional reading of Schechter presents him as a scholar, a practitioner of the Science of Judaism. However, Schechter's parody of the Hasidic movement, its masters and its adherents, written in the mid-late 1870's, suggests that even as Schechter engaged in rigorous scholarship he also worked as a creative artist. He associated with Jewish thinkers, writers and activists such as Peretz Smolenskin, and like them he created art for the sake of wrestling with the vital issues in Jewish life. His writing experiments enhanced his self-discovery. The text enables us to glimpse Schechter at an early period of his journey from his Romanian Hasidic family and community to a modern self, one with multiple identities, the relations of which shifted over time. His parody drew from the tradition of literary mystifications and was in dialogue simultaneously with the Sipurei Ma'asiyot, hagiographic stories about Hasidic masters, and with Joseph Perl's anti-Hasidic satire Megaleh temirin (Revealer of Secrets). Schechter's parody of Hasidism ironically contained both appreciation of this major modern movement of religious enthusiasm and criticism of its foes, revealing Schechter's eclectic nature and discomfort with committing fully to any trends in his contemporary Judaism.